A collaborative effort to frame and assess a social learning space for wheelchair curling coaches - Duarte, T. (University of Ottawa, 2020)
Social learning interventions have been implemented to develop coaches in many contexts, however are yet to be applied to coaches of athletes with disabilities. The lack of knowledgeable coaches prevents people with disabilities from participating in sports. The overall purpose of this doctoral research programme was to enhance the learning capability of the Canadian wheelchair curling coaches` landscape. To achieve this overall purpose, the study was divided in three phases (i.e., pre-intervention, framing, and assessment). The pre-intervention phase aimed at understanding the disability sport coaches` landscape; the framing phase aimed at building on the pre-intervention findings to frame a social learning space intervention for disability sport coaches; finally, the assessment phase, as the name suggests, assessed the value created through the intervention. More specifically, the four articles presented in this dissertation illustrate the work done to achieve the overall purpose of enhancing the learning capability of Canadian wheelchair curling coaches. The pre-intervention phase includes Article 1 and Article 2. Article 1 is a literature review of the two major areas addressed in this dissertation, which are disability sport in Canada and coach development. Article 2 introduces the metaphor of a landscape to create a visual representation via a map that includes the major elements of the Canadian wheelchair curling coaches` landscape. Semi-structured interviews with 16 participants were thematically analyzed and helped create the above-mentioned elements, such as the coaches` pathways, the types of learning structures, and the barriers. Moreover, Article 2 provides three considerations for systems conveners who seek to lead social learning space interventions in landscapes. Next, the framing phase took place concurrently with the assessment phase. Common to both phases, the intervention included a series of face-to-face and online interactions through the use of four online tools. Multiple data generation techniques (e.g., in-depth interviews, focus groups, observations) were employed during a 13-month period and resulted in 615 single-spaced pages of data. Thematic and interpretative analyses were used to make sense of the data. The framing phase, as presented in Article 3, includes the process through which the researchers (N = 3) made use of collaborative inquiry to co-construct the intervention with the participant coaches (N = 16) and Curling Canada technical leaders (N = 6). Additionally, Article 3 built upon the considerations from the pre-intervention phase to report how the intervention managed the limitations of the landscape, prioritized meaningful learning, incorporated influential people, as well as produced reflections on the consequences of the lack of enabling conditions. Article 4 expands the landscape metaphor and presents four composite vignettes of the participants according to their wheelchair curling coaching experiences. The vignettes vividly illustrate major contextual factors of the landscape common to all participants and the range of values created in the intervention. Overall, the findings of this dissertation contribute theoretically, methodologically, and practically in several ways. From a theoretical perspective, it is the first study to date to make use of landscapes of practice and the value creation framework to increase the learning capability of disability sport coaches. From a methodological perspective, the articles included in this dissertation made use of multiple and longitudinal data generation techniques to provide a broader perspective of the values created. Finally, the use of visual representations like the map and the vignettes, while unconventional, might facilitate the knowledge transfer for coaches and coach developers willing to frame social learning space interventions.